Redesign Packaging of Tempe Products Using Kansei Engineering Method in MSME Jaya Makmur Lumajang - Akbar Kurniawan Prasetyo; Akmal Suryadi (Universitas KH. Abdul Chalim Mojokerto, 2024)
The development of this growing era has given rise to competition between business people, making business people have to improve their strategies. MSME Jaya Makmur is a business that operates in the Tempe trading sector. MSME Jaya Makmur produces soybean tempeh which has a total production of approximately 100 kg per day. Apart from being hampered by the lack of identity on the packaging, the owner of MSME Jaya Makmur realizes that the packaging is still very simple and requires development and innovation that focuses on consumer desires to be able to compete with competitors' products. Therefore, it is necessary to redesign packaging (re-design) to develop tempeh product sales. Packaging also plays a very important role in product marketing. Apart from being hampered by the lack of identity on the packaging, the owner of MSME Jaya Makmur realizes that the packaging is still very simple and requires development and innovation that focuses on consumer desires to be able to compete with competitors' products. Therefore, it is necessary to redesign packaging (re-design) to develop tempeh product sales. Packaging also plays a very important role in product marketing. Keywords: Packaging Redesign, Tempe Products, MSME Jaya Makmur Lumajang